PROFESIONALISME PENYIDIK DIREKTORAT RESERSE KRIMINAL UMUM POLDA SULAWESI SELATAN - ISMAIL, ISMAIL; ILHAM, ILHAM (Patria Artha University, 2024)
The aim of this research is to determine the influence of education, training and work experience on the professionalism of investigators at the General Crime Directorate of the South Sulawesi Regional Police. This type of research is quantitative research using a questionnaire as a data collection tool with a sample size of 61 investigators and assistant investigators at the General Criminal Investigation Directorate of the South Sulawesi Regional Police. The analytical method used is multiple linear regression analysis. The results of multiple linear regression analysis show that partially the variables of education and work experience have a significant effect, while training has no effect on the professionalism of investigators at the South Sulawesi Regional Police's General Criminal Investigation Directorate. and simultaneously the variables of education, training and work experience jointly influence the professionalism of investigators at the South Sulawesi Regional Police's General Criminal Investigation Directorate.